Work-Life Balance and Digital Competence on Employee Retention with Employee Engagement as a Mediating Variable - Bambang Sukajie; Rian Andriani (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Employee retention is a critical challenge for startups operating in dynamic labor markets. This study examines the effects of work-life balance and digital competence on employee retention, with employee engagement as a mediating variable. This study was conducted among 250 service sector employees in Jakarta, Bandung, and Yogyakarta. This study uses a quantitative approach employing SEM-PLS analysis. The results reveal that work-life balance positively influences employee engagement and employee retention. Similarly, digital competence significantly affects employee engagement and employee retention. Employee engagement itself strongly predicts employee retention and mediates the relationship between work-life balance and retention as well as digital competence and retention. These findings highlight that enhancing work-life balance and developing digital competence are essential strategies to foster employee engagement, which in turn strengthens retention. The study underscores the strategic role of employee engagement as a mediator in translating human resource practices into long-term commitment, offering practical insights for startups to maintain a productive, adaptive, and loyal workforce in competitive digital environments.